Aunque tú no lo sepas : la poesía de Luís García Montero - Arnáiz, Charlie, 1975-; Ortega, Alberto, 1983- (Por amor al arte producciones S.L., 2016)
Documentary film that tries to bring to the public the figure and work of the Spanish poet Luis García Montero.--